Factor Analysis in the Implementation of Early Warning System Documentation in Psychiatric Hospitals - Nurul Mawaddah; Anndy Prastya; Bernadius Bogohanto (The Indonesian Journal of Occupational Safety and Health)
Introduction: An early warning system (EWS) is a tool to rapidly identify patient deterioration and prevent adverse events. However, the implementation and documentation have not been carried out optimally. This study aims to analyze factors related to the implementation of EWS documentation in a psychiatric hospital in Malang. Methods: The study was an analytical observational study with a cross-sectional design. The study population was all nurses in the intensive care unit of the hospital, with a total sample of 60 respondents selected using a proportional random sampling technique. Data collection used demographic data questionnaires, workload questionnaires, and observation sheets for the implementation of EWS documentation of patients through the hospital management information system. Analysis of the data used the chi-square test. Results: Implementation of EWS documentation was significantly related to workload and EWS training (p<0.05). Implementation of EWS documentation was not related to age, gender, education level, years of service, employment status, and work shift (p>0.05). Conclusion: Nurses with light workloads and who had attended EWS training created good documentation successfully (100%). Hospitals need to review their management in planning, developing, and fostering nursing resources, especially the provision of continuous training accompanied by equitable EWS monitoring for nurses in psychiatric hospitals.